2016
DOI: 10.3324/haematol.2016.145888
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-deep sequencing leads to earlier and more sensitive detection of the tyrosine kinase inhibitor resistance mutation T315I in chronic myeloid leukemia

Abstract: © Ferrata Storti Foundation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Therefore, the data are not sufficient to make suggestions regarding the choice of the TKI in the second-or subsequent-line setting, apart from the differential sensitivity in patients with the presence of BCR-ABL1 point mutations (Table 6). Because the detection of a mutation is the only factor that can specifically guide the choice of another TKI, 85 when a switch is planned for resistance/failure, a mutational analysis should always be performed using at least Sanger sequencing (SS), and whenever possible using next-generation sequencing (NGS), which is not yet widely available, but being more sensitive than SS [86][87][88][89][90] can avoid a wrong choice in up to 25% of cases. Whether mutational analysis should be performed in the case of nonoptimal response has been debated, but a consensus was not reached.…”
Section: The Choice Of the Tki: After First-linementioning
confidence: 99%
“…Therefore, the data are not sufficient to make suggestions regarding the choice of the TKI in the second-or subsequent-line setting, apart from the differential sensitivity in patients with the presence of BCR-ABL1 point mutations (Table 6). Because the detection of a mutation is the only factor that can specifically guide the choice of another TKI, 85 when a switch is planned for resistance/failure, a mutational analysis should always be performed using at least Sanger sequencing (SS), and whenever possible using next-generation sequencing (NGS), which is not yet widely available, but being more sensitive than SS [86][87][88][89][90] can avoid a wrong choice in up to 25% of cases. Whether mutational analysis should be performed in the case of nonoptimal response has been debated, but a consensus was not reached.…”
Section: The Choice Of the Tki: After First-linementioning
confidence: 99%
“…Next‐generation sequencing (NGS) as an alternative method can provide enhanced sensitivity and earlier mutation detection. The NGS platform used most frequently for BCR‐ABL1 KD sequencing is 454 from Roche (Basel, Switzerland) (Machova Polakova et al ., ; Baer et al ., ; Soverini et al ., ; Erbilgin et al ., ). The use of Ion Torrent (Thermo Fisher Scientific, Waltham, MA, USA) technology and the widely implemented Illumina (San Diego, CA, USA) platform has been reported by fewer authors to date (Eyal et al ., ; Deininger et al ., ; Kizilors et al ., ).…”
mentioning
confidence: 97%
“…Lately, several NGS/Sanger comparison studies reported that Sanger sequencing had misclassified or underestimated kinase domain mutation status in up to 55% of samples, where mutations with 1-15% abundance were detected by NGS [10,25]. Other publications also demonstrated that NGS systems are able to detect mutation at much earlier time and, therefore, having higher predictive value of emerging drug-resistance mutation [9,26,27]. In our study, all detected mutations by NGS had minimum coverage of 5,000x, which allowed the detection sensitivity to 1% and below.…”
Section: Resultsmentioning
confidence: 97%